2018
DOI: 10.25135/rnp.46.17.09.155
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Flaxseed (Linum usitatissimum L.) shell and Analysis of Its Polyphenol Contents by LC-MS/MS

Abstract: Flaxseed (Linum usitatissimum L.) is important source of oil and protein for industrial, pharmaceutical, and nutritional applications. In order to estimate the effects of lyophilized aqueous extract of flaxseed shell (AEF) and evaporated ethanolic extract of flaxseed shell (EEF), we studied their DPPH, ABTS, DMPD and O 2•-scavenging effects. 3+ reducing ability, and Fe 2+ chelating activity. Also, α-tocopherol, BHA, trolox, and BHT were used as positive controls. The results clearly AEF and EEF demonstrated ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…The CUPRAC assay is rapid, stable, cheap, selective, and suitable. [97] DPPH· and ABTS ·+ radical scavenging assays are the most putative and applicable methods to determine of the antioxidant capacities and radical scavenging effects of beverages, foods and plants. The DPPH· scavenging ability is the most common and oldest method for determining the antioxidant activities.…”
Section: Antioxidant Resultsmentioning
confidence: 99%
“…The CUPRAC assay is rapid, stable, cheap, selective, and suitable. [97] DPPH· and ABTS ·+ radical scavenging assays are the most putative and applicable methods to determine of the antioxidant capacities and radical scavenging effects of beverages, foods and plants. The DPPH· scavenging ability is the most common and oldest method for determining the antioxidant activities.…”
Section: Antioxidant Resultsmentioning
confidence: 99%
“…Our result also exhibits the presence of sinapic and p-coumaric acid in LUE; however, the extract was rich in gallic acid ferulic, and vanillic acid. Han et al (2018) reported the ability of the ethanolic and aqueous extract of flaxseed shell to scavenge DPPH radical with 49.50 and 53.30 μg/mL that was less than LUE activity. On the other hand, the ability of their extract to chelate ferrous ions 9.24 and 8.88 μg/mL was more than the extract of this research.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits are supposed to contain diversified bioactive compounds, which demonstrate biological activity in terms of antioxidant, antimicrobial and anticancer properties. These chemical classes have considerable disease preventing and health promoting effects on human body (Han et al, 2018).…”
Section: Estimation Of Total Phenolic Contents Flavonoids Contents Amentioning
confidence: 99%